2023
DOI: 10.1155/2023/3461121
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Mental Health Literacy on Psychological Resilience and Psychological Distress of Medical College Students

Abstract: Purpose. Psychological resilience plays an important role in relieving the psychological distress. However, little is known about its underlying mechanisms. Mental health literacy, an important way to promote mental health, may mediate the effect of psychological resilience on psychological distress. This study aimed to explore the relationship between mental health literacy, psychological resilience, and psychological distress and explore the mediating effect between psychological resilience and psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The results of the study suggest that better knowledge regarding mental health disorders may be beneficial for one's resilience. Recently, studies conducted among Chinese adolescents, college students and older Chinese individuals revealed that MHL was positively associated with resilience (Song et al, 2023;Zhang et al, 2023aZhang et al, , 2023b. MHL is associated with self-management and self-efficacy as well as with positive coping styles (Song et al, 2023;Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study suggest that better knowledge regarding mental health disorders may be beneficial for one's resilience. Recently, studies conducted among Chinese adolescents, college students and older Chinese individuals revealed that MHL was positively associated with resilience (Song et al, 2023;Zhang et al, 2023aZhang et al, , 2023b. MHL is associated with self-management and self-efficacy as well as with positive coping styles (Song et al, 2023;Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The association between MHL and resilience has not received much research attention. We found only three studies in which the association between MHL and resilience was examined, and these studies were conducted among Chinese adolescents (Zhang et al , 2023b), Chinese college students (Zhang et al , 2023a) and “empty nesters” in China (older individuals over 60 with no children or whose children are not around) (Song et al , 2023). In all of these studies, MHL was positively associated with resilience.…”
mentioning
confidence: 99%
“…Finally, AI can also be used for mental health education and the development of self-service tools. It can provide customized advice, training, and resources to help students improve their emotional intelligence and ability to cope with stress [5] .…”
Section: The Potential Of Artificial Intelligence In Psychological Co...mentioning
confidence: 99%
“…Psychological resilience is closely connected to both health competence and health status. Research has demonstrated that individuals with higher levels of psychological resilience exhibit greater mental health literacy, thereby enhancing their overall mental well-being [ 31 ]. According to family systems theory, the family, functioning as an emotional system, has the power to influence the psychological state of its members, subsequently influencing the health outcomes of individuals [ 1 ].…”
Section: Introductionmentioning
confidence: 99%